ANALISIS POSTUR KERJA DAN GERAKAN BERULANG TERHADAP KELUHAN MUSKULOSKELETAL DISORDERS PADA PEKERJA PEMBUATAN TEMPE DI DESA BANDUNG REJO KECAMATAN MRANGGEN KABUPATEN DEMAK - MUhammad Dhiyaudzihni Habibie; Suroto Suroto; Siswi Jayanti (Jurnal Kesehatan Masyarakat (Undip), 2017)
Odd work posture can have a risk on musculoskeletal disorders complaint. The inflicted effect is complaint on musculoskeletal system that perceived from very mild to very pain. Aspects to be considered in this case is the work posture that is various positions of the worker’s body during the work activities and repetitive motion is the same motion which is done by the worker during time period. The purpose of this research was to analyze work posture and repetitive motion with musculoskeletal disorders complaint on tempe manufacture workers in Bandung Rejo Village, Mranggen District, Demak Regency.This research was using descriptive approach with qualitative method. The research subjects consisted of 1 male worker who did the boiling process of soybean to yeast distribution and 3 female workers in the soybean packing process. Triangulation tools in this research was observation result with Baseline Risk Identification of Ergonomic (BRIEF) method. There were 9 observed working postures, which were: hand and right and left wrists, right and left elbows, right and left shoulders, neck, back and legs. The assesment mentioned, that there were 25 high riks, 41 average risks, 3 low risks and 3 not at risk. The interviewed results showed that 2 workers had very high MSDs complaints and the other 2 workers had high MSDs complaints. Workers should implement the safe work posture which was not doing the odd work posture during working and stretching was needed to overcome musculoskeletal disorders.